Multilingualism in the Baltic States Societal Discourses and Contact Phenomena - Lazdiņa, Sanita; Marten, Heiko F. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This edited collection provides an overview of linguistic diversity, societal discourses and interaction between majorities and minorities in the Baltic States. It presents a wide range of methods and research paradigms including folk linguistics, discourse analysis, narrative analyses, code alternation, ethnographic observations, language learning motivation, languages in education and language acquisition. Grouped thematically, its chapters examine regional varieties and minority languages (Latgalian, Võro, urban dialects in Lithuania, Polish in Lithuania); the integration of the Russian language and its speakers; and the role of international languages like English in Baltic societies. The editors' introductory and concluding chapters provide a comparative perspective that situates these issues within the particular history of the region and broader debates on language and nationalism at a time of both increased globalization and ethno-regionalism. This book will appeal in particular to students and scholars of multilingualism, sociolinguistics, language discourses and language policy, and provide a valuable resource for researchers in the related fields of history, political science, sociology, anthropology working on the Baltic States, Northern Europe and the post-Soviet world. Sanita Lazdiņa is Professor in Applied Linguistics at Rēzekne Academy of Technologies, Latvia. Her research interests include language and educational policies, multilingualism in the Baltics, linguistic landscapes, Latgalian, and folk linguistics. She is the editor of several publications on language acquisition, bilingual education and CLIL in Latvia. Heiko F. Marten is Director of the DAAD Information Centre Riga and Senior Researcher and Lecturer at the University of Latvia and Rēzekne Academy of Technologies, Latvia. His research focuses on language policy, linguistic landscapes, language learningmotivation, minorities and discourses on language. He is the author of Sprachenpolitik: Eine Einführung (2016) and co-editor of Minority Languages in the Linguistic Landscape (2012, with Durk Gorter and Luk Van Mensel).